Tree planting for poverty reduction in less-favored areas of the Ethiopian highlands - Holden, S.; Benin, Samuel; Shiferaw, B.; Pender, J.L. (2003)
This paper assesses the potential impact of planting of eucalypt trees as a strategy to reduce poverty in a less-favoured area of the highlands of Ethiopia. Results from simulations with a bio-economic model for a less-favoured case study area in the highlands are combined with survey data at community, household and plot level to assess how general the results of the bio-economic model are. Application of the bio-economic model shows clearly that land degradation, population growth, stagnant technology and drought threaten food security. Household welfare and land quality are deteriorating rapidly in the area and interventions are urgently needed to avoid human disaster. Planting of eucalypts on land unsuitable for crop production may substantially increase household incomes if market outlets for trees can be found. Tree planting will not have severe negative effects on food production or land conservation. A policy combining promotion of tree planting and conservation of cropland may achieve win-win benefits in terms of increased household incomes as well as more sustainable land-use. Analysis of survey data from the Amhara Region of Ethiopia reveals that there is a large area of land that is unsuitable for crop production located close to all-weather roads in the less-favoured areas of the region. Few trees have been planted on this type of land up to now. The past policy seems to have discouraged tree planting except on homestead plots that are more suitable for food crops.